Pengaruh Migrasi Masuk, Pendidikan dan Upah Minimum terhadap Pengangguran Terbuka di Kabupaten dan Kota Provinsi Jawa Timur - Candra Gunawan Wibisono (Airlangga Development Journal, 2020)
This research aims to analyze the influence of variable on migration, education and the minimum wage of open unemployment in regency/cities East Java province in 2009-2012 either simultaneously or partial. This research uses panel data (2009-2012) expectedly for migration, education, minimum wage and open unemployment variable. The sample ranges round 38 regency/cities in East Java. The model is choice use approach to analyze this problem is Fixed Effect Model (FEM). From the results of estimation is obtain that the migration variable entry and minimum wage significantly affect open unemployment. While the level of education variables have no effect on the open unemployment.